Nanoscale electrical investigation of layer-by-layer grown molecular wires - Musumeci, Chiara; Schuster, Swen; Zharnikov, Michael (Advanced materials, 2014)
Nanoscopic metal-molecule-metal junctions consisting of Fe-bis(terpyridine)-based ordered nanostructures are grown in layer-by-layer fashion on a solid support. Hopping is demonstrated as the main charge-transport mechanism both experimentally and theoretically.